Particle-Size-Dependent Delivery of Antitumoral miRNA Using Targeted Mesoporous Silica Nanoparticles - Lisa Haddick; Wei Zhang; Sören Reinhard; Karin Möller; Hanna Engelke; Ernst Wagner; Thomas Bein (MDPI AG, 2020)
Multifunctional core-shell mesoporous silica nanoparticles (MSN) were tailored in size ranging from 60 to 160 nm as delivery agents for antitumoral microRNA (miRNA). The positively charged particle core with a pore diameter of about 5 nm and a stellate pore morphology allowed for an internal, protective adsorption of the fragile miRNA cargo. A negatively charged particle surface enabled the association of a deliberately designed block copolymer with the MSN shell by charge-matching, simultaneously acting as a capping as well as endosomal release agent. Furthermore, the copolymer was functionalized with the peptide ligand GE11 targeting the epidermal growth factor receptor, EGFR. These multifunctional nanoparticles showed an enhanced uptake into EGFR-overexpressing T24 bladder cancer cells through receptor-mediated cellular internalization. A luciferase gene knock-down of up to 65% and additional antitumoral effects such as a decreased cell migration as well as changes in cell cycle were observed. We demonstrate that nanoparticles with a diameter of 160 nm show the fastest cellular internalization after a very short incubation time of 45 min and produce the highest level of gene knock-down.